Identifying avian malaria vectors: sampling methods influence outcomes - Carlson, Jenny S.; Walther, Erika; TroutFryxell, Rebecca; Staley, Sarah; Tell, Lisa A.; Sehgal, Ravinder N. M.; Barker, Christopher M.; Cornel, Anthony J. (Parasites & vectors, 2015)
Background The role of vectors in the transmission of avian malaria parasites is currently understudied. Many studies that investigate parasite-vector relationships use limited trapping techniques and/or identify potential competent vectors in the field in such ways that cannot distinguish between an infected or infectious vector. Without the use of multiple trapping techniques that address the specific biology of diverse mosquito species, and without looking at the infection status of individual mosquitoes, it is not possible to make dependable conclusions on the role of mosquitoes in the transmission of avian malaria parasites. Methods We conducted two years of mosquito collections at a riparian preserve in California where a wide diversity of species were collected with multiple trap types. We hypothesized that competent mosquito species can influence the distribution and diversity of avian malaria parasites by acting as a compatibility filter for specific Plasmodium species. To determine the infection status of all individual mosquitoes for Plasmodium species/lineages, amplification within the cytochrome b gene was carried out on over 3000 individual mosquito thoraxes, and for those that tested positive we then repeated the same process for abdomens and salivary glands. Results Our data show heterogeneity in the transmissibility of Plasmodium among ornithophillic mosquito species . More specifically, Culex stigmatosoma appears to not be a vector of Plasmodium homopolare , a parasite that is prevalent in the avian population, but is a vector of multiple other Plasmodium species/lineages. Conclusions Our results suggest that conclusions made on the role of vectors from studies that do not use different mosquito trapping methods should be re-evaluated with caution, as we documented the potential for trapping biases, which may cause studies to miss important roles of specific mosquito species in the transmission of avian malaria. Moreover, we document heterogeneity in the transmission of Plasmodium spp. by mosquitoes can influence Plasmodium diversity and prevalence in specific locations to Plasmodium- vector incompatibilities.